Systemy informacyjne zarządzania projektami w przedsiębiorstwie - Wąsowicz, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article describes the innovation in Project Management Office (PMO). First of all, they are novelties in service of PMO, which raise the effectiveness of the project management. The author mentions the main advantages and risk, that result from introducing Project Management Office in the company. The author also describes some results a poll concerning the implementation on of PMO in Polish companies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 116-123